Struggle Against Gender Inequality in Anne with an E (2019) - R. Ay Sulthania Bilqis (LITERA KULTURA : Journal of Literary and Cultural Studies, 2022)
This study examines gender inequality in Anne with an E (2019) and how it affects the main character. Gender inequality includes women exploitation, victims of sexual harassment, no freedom of the press, women and education, barriers to women's education, unequal right at work, exploring gendered expression and sexuality, and racial segregation and discrimination. This study used Marxist Feminism as a theory. Marx's approach has provided us with the tools and ideas that allow us to think about feminism, class, and anti-capitalism all at once. Marxist feminism and historicism understanding reproduction concerning production may assist people in better comprehending how exploited and abused women are under capitalism. The feminist Netflix series Anne with an E (2019) brings up various still-relevant societal topics from the 1900s, including unequal treatment between men and women. The purpose of this study is to see how the movie Anne with an E Season 3 faced gender inequality in education. Gender inequality issues in the movie matched with Marxist Feminism. The result of this study shows how gender inequality is depicted, such as women's exploitation, including child abuse, unequal right at work, and barriers to girls’ education. Those make the main character react to the inequality and bring out to women's liberation movement